Economic crisis and labour force transition to inactivity: A comparative study in German rural and urban areas - Ilkay Unay Gailhard; Karin Kataria (Studies in Agricultural Economics, 2014)
This study analyses the determinants of labour force transition to inactivity in the German labour market. Using German Labour Force Survey data the influence on the transition flow to inactivity of factors such as age, education, marital status, sex and registration with the public employment service are examined. We present estimates of degree of urbanisation-specific multinominal logit models to analyse the determinants of individuals' transition probabilities in rural and urban areas. By comparing the influence of the factors that affect transition to inactivity before (2002-07) and during (2008-09) the global economic crisis, this paper contributes to the general understanding of transitional labour market flow dynamics during the crisis period. The findings suggest that during the crisis period education level and marital status have had different impacts in rural and urban regions on the transition to inactivity. While these two factors influenced the transition to inactivity before the crisis, their effect has been stronger during it. Additionally the results suggest that the interaction of individuals with institutional settings (e.g. registration with the public employment service) have to be taken into account when designing active labour market policy measures, especially during crisis periods. Knowledge about the influence of these factors on the transition to inactivity, and their different effects in rural and urban areas, provides important information for designing policies aiming to reduce the transition to inactivity during crisis periods.
Keywords: 330; labour force transition; inactivity; economic crisis; rural and urban areas; multinominal logit model; Germany